Islamic social finance and the imperative for social impact measurement - Syed Azman, Syed Marwan Mujahid; Engku Ali, Engku Rabiah Adawiah (IIUM Press, International Islamic University Malaysia, 2019)
This paper aims to highlight the imperative of social impact measurements in Islamic finance by exploring the growing interest of Islamic social finance and social impact. From critical review of literature, the paper finds that despite the tremendous growth of the Islamic finance industry, little is known about how Islamic finance institutions measure their social values, and how they report their social impact. The ongoing criticisms of Islamic finance failing to fulfil its “raison d’etre” and underlying objectives provides an indication of that there is a gap between its theory and practice. More focus towards developing Islamic social finance and integrating Islamic financial instruments with the mainstream social finance spectrum may help address these criticisms. In doing so, the paper posits the need to expand the definition of Islamic social finance beyond just zakāt, waqf and Islamic microfinance. Furthermore, the paper also proposes that mechanisms or frameworks for Islamic financial institutions to measure the social impact of their operations, products and services should be developed to realise the full potential of Islamic finance. This can be done through a stakeholder-based approach and assimilating frameworks of Value-Based Intermediation, Maqāṣid al-Sharīʽah, and Sustainable Development Goals.